On the occurrence of a Palaearctic species of the genus Aphaereta Foerster (Braconidae, Alysiinae) and description of a new species of the genus Leiophron Nees (Braconidae, Euphorinae) from central India - Gupta, Ankita; van Achterberg, Cornelis; Pattar, Rohit; Minz, Kriti Arpana (Zootaxa, 2022)
A new species of parasitoid wasp, Leiophron crassivena Gupta & van Achterberg sp. nov. (Braconidae, Euphorinae), is described and illustrated from central India along with first report of the Palaearctic species Aphaereta vondelparkensis van Achterberg et al. (Braconidae, Alysiinae) from India.